Efficacy of educational management and mathematics: Implications for accounting education and practice in Nigeria - Nweze, Bernardine Ngozi; Ndubuisi, Chukwu Peter; Eze, Thecla Amogechukwu; Chukwuma, Onyia Basil; Sochima, Unodiaku Stanislus (Nurture, 2025)
Purpose: The main purpose of the research is to confirm whether Mathematics and Educational Management have implications for the effective study of accounting and its practice in Nigeria. These tendencies were understood as an emphasis on making the course learning objectives of accounting relevant in terms of skills and competencies for the labor market, management strategies, fund management, and analyzing complex financial data, among others. The study was therefore aimed at providing answers to seven (7) research questions and testing four (4) hypotheses at a significance level of P ≤ 0.05. Design/Methodology/Approach: The study adopted a survey research design. A self-constructed questionnaire instrument developed by the researchers was used to collect data from a random sample of undergraduates from public and private universities. Mean, standard deviation (SD), and t-test statistics were used to analyze the data. Findings: Results revealed that nine mathematics and statistics topics and nine basic managerial skills/competencies were found to be required for effective accounting professional practice. Both male and female students strongly agreed that eleven mathematics and statistics skills and nine managerial skills contributed significantly (P≤0.05) to effective performance and practice of accounting. Moreover, students in public and private universities strongly agreed that the nine mathematical skills and nine managerial skills/competencies contribute significantly (P≤0.05) to the effective performance of practicing accountants. Conclusion: Mathematics and educational management are crucial for the effective study and practice of accounting. Research Limitations/Implications: The study was limited to two schools (one public and one private university) only. The study has implications for the type of school, such that irrespective of whether the school is public or private, the acquisition of mathematics and managerial skills/competencies is paramount to successful accounting practice. Practical Implications: Both male and female undergraduates who successfully acquire mathematics and managerial skills during their schooling will be able to perform effectively in accounting as practicing accountants. Contribution to Literature: The findings of the study will provide updated information on research concerning the efficacy of mathematics and educational management skills/competences in the study of accounting at universities.